2014
DOI: 10.1007/s10867-014-9341-4
|View full text |Cite
|
Sign up to set email alerts
|

THz time scale structural rearrangements and binding modes in lysozyme-ligand interactions

Abstract: Predicting the conformational changes in proteins that are relevant for substrate binding is an ongoing challenge in the aim of elucidating the functional states of proteins. The motions that are induced by protein-ligand interactions are governed by the protein global modes. Our measurements indicate that the detected changes in the global backbone motion of the enzyme upon binding reflect a shift from the large-scale collective dominant mode in the unbound state towards a functional twisting deformation that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
4
14
0
Order By: Relevance
“…For example in Fig. 4a, the peaks at approximately 150 cm −1 and 140 cm −1 in the dark-state spectrum are likely associated with interhelical and solvent-induced H-bonding interactions52. An analysis of the H-bonding dynamics of the intra- and interhelical fluctuations in both states of the receptor from the MD simulations reveal peaks at a similar frequency, further confirming our assignments (Table 1).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…For example in Fig. 4a, the peaks at approximately 150 cm −1 and 140 cm −1 in the dark-state spectrum are likely associated with interhelical and solvent-induced H-bonding interactions52. An analysis of the H-bonding dynamics of the intra- and interhelical fluctuations in both states of the receptor from the MD simulations reveal peaks at a similar frequency, further confirming our assignments (Table 1).…”
Section: Resultssupporting
confidence: 84%
“…4a with the torsional oscillation of methyl groups of solvent-exposed helices in the receptor. From earlier experiments on other proteins4852 we have found that the experimentally determined 110 cm −1 peak is a general indicator of a flexible protein environment48. This supports our earlier notion that Meta II is more flexible than the dark-state receptor.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Then the vibration frequency structure information of ofloxacin was obtained by Gaussian 03 software. The dynamic vibration of ofloxacin in THz band was observed by Gaussian View software [7] [8]. Experimental results do not appear virtual frequency phenomenon, consistent with the actual situation.…”
Section: Experimental Preparationsupporting
confidence: 56%
“…This family of models has been shown to successfully capture global protein conformational fluctuations including low frequency modes . For the protein used here, lysozyme, this includes the widely studied hinge‐bending motion . Although the ENM is most often employed for Normal Mode Analysis, it can also be used in molecular dynamics simulations …”
Section: Methodsmentioning
confidence: 99%